Distributed fibre optic monitoring of damaged lining in double-arch tunnel and analysis of its deformation mode. (April 2021) - Sui, Yi; Cheng, Xiaohui; Wei, Jiaxu
Highlights: Distributed fibre optic monitoring was applied in the damaged double-arch tunnel. Lining deformation mode was explored based on strain profiles. An inversion analysis method based on fibre optic strain data was proposed. Abstract: Cracking and crushing were observed in the first tunnel lining of the Kaidagu double-arch tunnel (China), excavated in weathered surrounding rock. This concrete damage occurred during excavation of the second tunnel. It was necessary to monitor the continuous strain distribution along the entire cross section of the lining, so distributed fibre optic monitoring was carried out for nearly 1 year to study the deformation and stress of the damaged lining of the first tunnel. Optical fibres were attached to the inner surface of the concrete secondary lining and on opposite sides of the temporary arch support. Crack development was detected on the concrete lining, and the strain distribution indicated that vertical ovalisation and oblique ovalisation deformation was generated on the basis of the original deformation. Overall compression deformation was observed as this deformation mode developed over time. Ignoring the effects of axial force, the radial displacement of the concrete lining caused by the bending moment was calculated from the fibre optic strain data. The results were compared with those obtained using total stations, and obvious errors were found. According to the curved beam theory, a more accurate inversion analysis scheme based on the fibre optic strain data was proposed to determine the deformation mode of arch structures. The combined effect of the axial force and the bending moment was considered for the first time. This scheme was used to calculate the displacements, forces and loads of arch structures and was verified by finite-element simulations. The proposed method was applied to analyse the temporary arch support. The calculation results were consistent with those obtained using total stations and conformed with the tunnel deformation mode. The results and the proposed method are useful in explaining the subsequent deformation mode of the damaged lining in the first tunnel and provide valuable information for post-failure reinforcement.